The Process of Integrating Public Schools in Wichita, Kansas 1890-1971 - Schiff, Mitchel (Kansas State University, The Chapman Center for Rural Studies, 2014)
This document includes the following: a brief history of the Wichita Kansas segregated school system, including avoiding integration in the 1950’s. The study also addresses the legal process of integrating the Wichita schools in the late 1960’s. It uses city plat maps, census data, and legal analysis.
Mitchel Schiff, “The Process of Integrating Public Schools in Wichita, Kansas 1890-1971 ,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/229.
Keywords: Brown vs. Education; Integration; Kansas; Public Schools; Sedgwick County; Segregation